Exploring the viability of newer technologies in care and management of tribal diabetes and metabolic syndrome in India - Singh, Kritika; Chakma, Tapas; Ray, Suman; Vaidh, Neha; Shrivastava, Suyesh (International Journal of Research in Medical Sciences, 2024)
With the advancements of digitalization technology in health sector, diabetes care and management have also experienced modifications and betterment. Various newer technologies cater to the individual conditions and needs and provide a personalized treatment. Device based technologies such as continuous glucose monitoring (CGM) linked to closed loop insulin delivery system, insulin pumps, wearable devices linked with mobile apps have made the self-management of diabetes possible on regular basis. In its contrast, the technologies are yet to reach the tribal settings of India, and also very challenging to implement. Studies have shown that the scenario of diabetes prevalence in Indian tribal population is as crucial as urban population. Also, land alienation, lack of health management infrastructure, low connectivity, technological challenges add up to their condition. While various technologies are challenging to implement due to electricity, network connectivity, infrastructure and storage facilities, some technologies can be implemented easily with the joint approach of primary health care staff, governmental and non-governmental organizations and people with diabetes themselves. Digitization of data is needed as it will give a clearer picture of the prevalence, provide easy access for the follow ups and easier to implement intervention-based technologies. The situation demands a tailored multifaceted approach for implementing the technological based remedies in tribal settings of India as it will increase the quality of life in these areas.